2009
DOI: 10.1521/jscp.2009.28.5.577
|View full text |Cite
|
Sign up to set email alerts
|

Personality Traits and the Working Alliance in Psychotherapy Trainees: An Organizing Role for the Five Factor Model?

Abstract: Ackerman and Hilsenroth (2001, 2003) suggested that therapist personality may be meaningfully associated with the psychotherapy working alliance. We extended this line of research by examining the association between Five Factor Model (Costa & McCrae, 1997b) personality traits Neuroticism, Extraversion, Openness to Experience, Agreeableness, and Conscientiousness, and ratings of the working alliance made by clients and psychotherapy trainees. Higher trainee Neuroticism was associated with better client ratings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
2
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 37 publications
3
20
2
3
Order By: Relevance
“…They found that several therapist attributes (e.g., flexible, respectful, warm, and open) and several types of interventions (e.g., reflection, support, affirming, accurate interpretation, and facilitating affective expression) were associated with more positive alliances. Dispositional qualities of the therapist such as the Big Five traits (Chapman, Talbot, Tatman, & Britton, 2009) and compassion (Gilbert, 2009) are also plausible antecedents of the capacity to provide high levels of the Rogerian conditions. Second, psychotherapy researchers need to include multiple therapists in their designs whenever possible so as to permit the separation of between-therapist and within-therapist effects.…”
Section: Discussionmentioning
confidence: 99%
“…They found that several therapist attributes (e.g., flexible, respectful, warm, and open) and several types of interventions (e.g., reflection, support, affirming, accurate interpretation, and facilitating affective expression) were associated with more positive alliances. Dispositional qualities of the therapist such as the Big Five traits (Chapman, Talbot, Tatman, & Britton, 2009) and compassion (Gilbert, 2009) are also plausible antecedents of the capacity to provide high levels of the Rogerian conditions. Second, psychotherapy researchers need to include multiple therapists in their designs whenever possible so as to permit the separation of between-therapist and within-therapist effects.…”
Section: Discussionmentioning
confidence: 99%
“…Therapists' personality traits in particular have scarcely been researched so far (Lingiardi et al, 2017) but are also likely to be of influence in building a good working alliance (Chapman et al, 2009;Taber et al, 2011) as well as other therapeutic skills. Although there is a substantial amount of literature on which qualities and skills therapists should present (Keenan and Rubin, 2016), there is surprisingly little research on what therapists are actually like.…”
Section: Personality In Therapistsmentioning
confidence: 99%
“…Se resalta la importancia de realizar estudios a partir de la interacción entre terapeuta y paciente con el fin de conocer mejor las variables que influyen en el proceso terapéutico (como lo es el estilo personal del terapeuta); se considera que hay tres variables que contribuyen a la formación del estilo personal del terapeuta a saber la posición socio-profesional, la situación vital (la personalidad, la actitud y los posicionamientos) y, los modos dominantes de comunicación que utiliza (Castañeiras, Ledesma, Corbella et al, 2009;Corbella, Fernández, Saúl, García & Botella, 2008;Fernández, 1998;García & Rodríguez, 2005;Saarnio, 2010;Santibáñez et al, 2008;Shevade, Norris, & Swann, 2011;Topolinski & Hertel, 2006) En los estudios encontrados durante la investigación se halló que el terapeuta debe tener una personalidad madura, un profundo nivel de autoconocimiento y tener satisfechas sus necesidades bá-sicas, como características esenciales para lograr mejores resultados durante el proceso terapéutico, de no ser así, el terapeuta puede no permitir un desarrollo favorable del paciente y hasta puede influir produciendo cambios negativos; se concluyó que particularidades como la flexibilidad de aprendices, la honestidad, el respeto, la honradez, la confianza, el interés, la atención, la amabilidad, la calidez y, la apertura, se asocian con una alianza mejor y, que la incertidumbre, rigidez, criticidad, distancia, tensión, aislamiento y, distracción se asocian con una alianza peor (Ackerman & Hilsenroth 2003;Chapman 2009;Pack, 2011;Rial, Castañei-ras, García, Gömez & Fernández, 2006 …”
Section: Ntroducciónunclassified